Kesiapan dan Sikap Mahasiswa Program Studi Rekam Medis Terhadap Donor Darah Volunter - Muhammad Rizki; Emilia Arsita; Astry Axmalia (Medika Promkes : Jurnal Kreativitas Kesehatan, 2026)
Background: Health students have great potential as a source of quality blood donors if they are well-motivated. This study aims to determine the characteristics and level of blood donation interest among fifth-semester Medical Records students at the Bhakti Setya Indonesia Health Polytechnic. Methods: This quantitative study used a cross-sectional design. The sample size was 100 respondents selected using purposive sampling. Data analysis was conducted using univariate and frequency distribution. Results and Disscusions: Respondents were predominantly female (74%) and 72 respondents in the 21-year-old age group. The evaluation results showed that students' blood donation interest was high at 73% (73 respondents). Meanwhile, interest was moderate at 21% (21 respondents), and the lowest interest was 6% (6 respondents). Conclusion: Most fifth-semester Medical Records students have a high interest in voluntary blood donation.